THE EPHEMERAL FEAST: FOOD AND THE FRAGILITY OF THE HUMAN CONDITION IN FAE MYENNE NG’S BONE (International Journal of Food and Nutritional Sciences, 2022)
Abstract: In contemporary literature, food serves as a powerful metaphor for exploring existential crises, cultural identity, and the immigrant experience. In Bones, Fae Myenne Ng uses food to symbolize the complexities of displacement, memory, and cultural adaptation. The novel follows a Chinese immigrant family in San Francisco, focusing on themes of loss, longing, and generational conflict. Food, particularly the act of sharing meals, becomes a means of preserving cultural identity, while also reflecting the emotional and physical toll of migration. Through the experiences of the narrator's family, Ng explores the double-consciousness of bicultural and bilingual identities, as well as the racialized, gendered labour of immigrant women. Drawing on sociological theories, such as Pierre Bourdieu’s concepts of food practices and Lisa Lowe’s notion of a “flexible workforce,” the paper examines how food rituals both anchor and fragment cultural traditions, and dramatizes the challenges of assimilation, cultural negotiation, and the bittersweet realities of the immigrant journey.